2004
DOI: 10.1123/rsj.28.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Importance of Recreational Sport Management Competencies Based on Management Level, Agency Type, and Organizational Size

Abstract: While jobs in the recreational sport and fitness industry are gaining in popularity, research related to the specific knowledge base and competency areas required of recreational sport managers has been limited (Barcelona, 2001; Toh, 1997). The purpose of this study was to examine the differences in the perceived importance of recreational sport competencies based on managerial level, agency type, and organizational size. Data from 295 respondents reveals significant differences in the importance placed on com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…The professional development category focused on research related to the professional and academic needs of full-time and student employees in recreational sports organizations. These studies addressed topics such as student employment (e.g., Bower, Hums, Keedy, 2005;Miller & Grayson, 2006), internships (e.g., Ross & Beggs, 2007), job satisfaction (e.g., Kaltenbaugh, 2009;Pack, Jordan, Turner, & Dannell, 2007), career pathways (e.g., Ross & Schurger, 2007), recreational sport job competencies (e.g., Ball, Simpson, Ardovino, & Skemp-Arlt, 2008;Barcelona, 2004), and academic curriculum development (e.g., Jamieson & Toh, 2001;Young, Ross, & Barcelona, 2003). Less than one-fourth of the published manuscripts addressed issues related to professional and academic development in recreational sports (n = 15, 23.1%).…”
Section: Thematic Categoriesmentioning
confidence: 99%
“…The professional development category focused on research related to the professional and academic needs of full-time and student employees in recreational sports organizations. These studies addressed topics such as student employment (e.g., Bower, Hums, Keedy, 2005;Miller & Grayson, 2006), internships (e.g., Ross & Beggs, 2007), job satisfaction (e.g., Kaltenbaugh, 2009;Pack, Jordan, Turner, & Dannell, 2007), career pathways (e.g., Ross & Schurger, 2007), recreational sport job competencies (e.g., Ball, Simpson, Ardovino, & Skemp-Arlt, 2008;Barcelona, 2004), and academic curriculum development (e.g., Jamieson & Toh, 2001;Young, Ross, & Barcelona, 2003). Less than one-fourth of the published manuscripts addressed issues related to professional and academic development in recreational sports (n = 15, 23.1%).…”
Section: Thematic Categoriesmentioning
confidence: 99%
“…A study conducted by Arnold et al (1998) examined various employment settings of athletic trainers, and found that when hiring employees, experience was valued as well as holding degrees from different institutions. The following competency areas were found by Barcelona (2004) to be more important for upper-level administrators: communication/public relations, management techniques, business procedures, legality/risk management, computer skills, facilities/equipment management, and research/evaluation. Barcelona also found that substantial differences existed in the general body of knowledge necessary for upper-level and entry-level recreational sport managers.…”
Section: Various Expectations For Different Professionsmentioning
confidence: 99%
“…Upper-level sport administrators need to be more prepared in areas related to business administration, technology, research, evaluation, and various other types of management such as personnel, risk, facilities, and equipment. Furthermore, and interesting to note, is that entry-level competencies should be covered within undergraduate recreation or sport management curricula, while upper-level administrative competencies should be covered within graduate curricula or professional training programs (Barcelona, 2004). Longsdorf (2004), in a survey of parks and recreation professionals, found that potential employers in this field valued an employee who had strong communication skills.…”
Section: Various Expectations For Different Professionsmentioning
confidence: 99%
See 1 more Smart Citation
“…No que refere às competências dos gestores, as investigações no domínio da gestão do esporte têm explorado a sua aplicação a partir de diversas variáveis organizacionais, tais como nível hierárquico (1,17) , dimensão da organização (1,20) , setor de atuação (1,17) e formação académica (17) . Entre as várias competências apontadas na literatura como sendo importantes para gerir as organizações esportivas destacam-se, no presente estudo, aquelas relacionadas com a liderança.…”
Section: Introductionunclassified